THE IMPACT OF EGYPT’S GROSS DOMESTIC PRODUCT (GDP) ON THE VOLUME OF INDONESIA’S COFFEE EXPORTS (25-Year Data) - Elpawati; Zulmaneri; Muhammad Rifky Zulfikar (Syarif Hidayatullah State Islamic University Jakarta, 2026)
This study analyzes the effect of Egypt’s Gross Domestic Product (GDP, USD) on the volume of Indonesian coffee exports to Egypt (kg) (Harmonized System Code: 090111) over the period 2000–2024 using a simple regression method. The analysis is conducted based on the prediction that there is a relationship between two quantitative variables (GDP → export volume). The quality of the regression equation is assessed using the coefficient of determination, where , which measures the proportion of variability explained by the regression model. The results show that GDP has a positive and statistically significant effect on coffee exports (t = 9.49, p = 0,00000000202), with an Value of 0.796, and the F-test result was statistically significant (p < 0.001). These findings indicate that Egypt’s GDP has a statistically significant simultaneous effect on the volume of coffee exports (ceteris paribus). The R-squared value of 0.797 indicates that 79.7% of the variation in coffee export volume can be explained by Egypt’s GDP, while the remaining 20.3% is influenced by other factors outside the model.